Neural substrates of intention-consequence integration and its impact on reactive punishment in interpersonal transgression - Yu, H; Li, J; Zhou, X (Society for Neuroscience, 2015)
When evaluating interpersonal transgressions, people take into account both the consequential damage and the intention of the agent. The intention and consequence, however, do not always match, as is the case with accidents and failed attempts. We combined an interactive game and functional MRI to investigate the neural substrates underlying the processing of intention and consequence, and its bearing on reactive punishment. The participant interacted with anonymous partners, who decided to deliver pain stimulation either to himself/herself or to the participant to earn a monetary reward. In some cases, the decision was reversed by the computer. After pain delivery, the partner's intention was revealed. Unbeknownst to the partner, the participant was then allowed to punish the partner by reducing his/her monetary reward. Behaviorally, the punishment was lower in the accidental condition (unintended harm relative to intended harm) but higher in the failed-attempt condition (unintended no-harm relative to intended no-harm). Neurally, the left amygdala/hippocampus was activated in the conditions with blameworthy intention (i.e., intentional harm and failed attempt). The accidental (relative to intentional) harm activated the right temporoparietal junction (TPJ) and the anterior inferior frontal gyrus (IFG), while the failed attempt (relative to genuine no-harm) activated the anterior insula (AI) and the posterior IFG. Effective connectivity analysis revealed that in the unintentional conditions (i.e., accidental and failed attempt) the IFG received input from the TPJ and AI, and sent regulatory signals to the amygdala. These findings demonstrate that the processing of intention may gate the emotional responses to transgression and regulate subsequent reactive punishment.